MANAJEMEN TADRIB ASATIDZ DALAM MENGEMBANGKAN KEMAMPUAN PEDAGOGIK GURU - Elfara Hajjar Sujani; Erni Munastiwi (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
Teachers must possess personality, social, pedagogic, and professional competencies. In addition, educators must continue developing skills that support competence. One of the skills that educators must have is pedagogic ability. Tadrib asatidz is one of the learning methods that can be used to develop skills. For the tadrib asatidz method to be successful, good management is needed. The purpose of the study was to examine the management of tadrib asatidz in developing pedagogic abilities. The research method used is descriptive qualitative research. Data was obtained utilizing in-depth interviews, observation and documentation. The subjects in this study were 83 educators at the Al-Irsyad Al-Islamiyyah Tulungagung educational institution. The data analysis technique used data triangulation. The data collection techniques include reduction, data presentation, and synthesis withdrawal. The results showed that the management of tadrib asatidz in developing teachers' pedagogic abilities was carried out through the stages of planning (planner), implementation (implementation) and evaluation (evaluation). Through tadrib asatidz, teachers can develop all aspects of child development following learning and educational theories, develop curriculum, utilize digital technology, provide facilities for students, communicate well, conduct assessments and reflect